Long-term follow-up of intraocular lens implants: the first 127 compared with the latest 100 of the same style in a span of 9 years. Issue 6 (June 1984) - Noble, M.; Cheng, H.; Jacobs, P.; Salmon, J.; McPherson, K.
Abstract : The long-term follow up of the first 127 patients (127 eyes) treated by one surgeon with cataract extraction and Federov I lens implantation is reported. The proportion of patients achieving visual acuity of 6/12 or better had decreased since the one year follow-up. Corneal oedema was the most serious long-term complication. This group of patients is compared with the latest 100 patients (100 eyes) operated on by the same surgeon using the same type of implant. There was a reduction of some operative complications, and improvement in surgical techniques had resulted in a lower sample endothelial cell loss at one month.